el-Kâmil fi’t-târîh - 880-01 İbnü'l-Esîr, İzzeddin, 1160-1233. (Beyrut)
11 cilt (1. c. 697 sayfa ; 2. c. 579 sayfa ; 3. c. 537 sayfa ; 4. c. 602 sayfa ; 5. c. 629 sayfa ; 6. c. 545 sayfa ; 7. c. 570 sayfa ; 8. c. 734 sayfa ; 9. c. 676 sayfa ; 10. c. 711 sayfa ; 11. c. 585 sayfa)